Characterization and phylogenetic analysis of the chloroplast genome of galium spurium. Issue 3 (4th March 2023) - Yin, Hanbin; Huang, Kerui; Xie, Peng; Mo, Ping; Zhang, Ningyun; Wang, Yun
Abstract: Galium spurium is a farmland weed, with strong stress resistance. However, its chloroplast genome has never been reported. In this study, the complete sequence of the chloroplast genome of G. spurium was characterized, which is a circular molecule, 153, 481 bp in length, and with a large single copy region of 84, 334 bp, a small single copy region of 17, 057 bp, and a pair of inverted repeat regions of 26, 045 bp. The whole genome contained 127 genes, including 82 protein-coding genes, 37 transfer RNA genes, and eight ribosomal RNA genes. Phylogenetic analysis shows that it relates closely to G. aparine . This study provides a basis for the further phylogenic study of Galium.